Publisher Correction: Solvent-assisted programming of flat polymer sheets into reconfigurable and self-healing 3D structures - Yang Yang (Nature Portfolio, 2018)
The original version of this Article omitted the Received and Accepted dates; they should have been 21st January 2018 and 12th April 2018, respectively. This has been corrected in the PDF and HTML versions of the Article.